Endoscopic and histologic response to cyclosporine in ulcerative colitis and their impact on disease outcome: A cohort study. Issue 7 (July 2016) - Fron, Clémence; Pierry, Clémence; Poullenot, Florian; Chabrun, Edouard; Subtil, Clément; Capdepont, Maylis; Zerbib, Frank; Belleannée, Geneviève; Laharie, David
Abstract: Introduction: Cyclosporine (CsA) is an effective agent for treating patients with acute steroid-refractory ulcerative colitis (UC). The aim was to assess endoscopic and histologic responses to CsA and to determine their predictive value on UC outcome. Patients and methods: Consecutive UC patients who received intravenous CsA for an acute refractory UC were included when they had endoscopic assessments with biopsies at entry and, at CsA interruption in responders. Mucosal healing (MH) was defined by Mayo endoscopic subscore ≤1 and, histologic response (HR) by the absence of basal plasmocytosis or a Geboes score <3.1. Results: Among 21 patients who responded to CsA, MH was achieved in 81%. Survival rates without relapse at 2 years were 79% and 25% in patients with MH and without MH, respectively ( p  = 0.04). HR was observed in 84% of patients according to basal plasmocytosis and in 68% according to Geboes score. Multivariate analysis revealed that a Mayo endoscopic subscore of 0 was the only prognostic factor associated with absence of relapse (RR = 12; 95%CI: 1.05–136.79). Conclusion: CsA provides MH and HR in most of UC patients responding to this drug. As suggested with other UC treatments, a complete MH with CsA has a good prognostic value.